O consumo e a percepção da vida útil dos eletroeletrônicos em decorrência da pandemia causada pela Covid-19, entre 2020 e 2023, no estado de São Paulo - Nardon, Nicole Eduarda (Universidade Federal de São Carlos, 2023)
The generation of waste electrical and electronic equipment (WEEE) is one of the fastest growing in the world and in this perspective the study sought to evaluate consumer behavior in relation to the disposal and consumption of electrical and electronic equipment, with a focus on cell phones and notebooks, during the pandemic period caused by COVID-19, between 2020 and 2023, understanding the perception of useful life, the period of exchange or purchase and the reasons for their disposal in the population of the state of São Paulo. The analyses performed were based on the theoretical framework and on a sample of 394 people, who answered an online questionnaire. The study evaluated the main reasons for disposing of cell phones, which are related to damage or non-functioning of the device and the lack of additional resources. And for notebooks, it includes the need to perform work- and study-related tasks. In addition, the storage of devices after active use was predominant in the survey, where respondents prefer to keep them, with the intention of using the device at some other time. The concept of planned obsolescence was also explored in this study, whereby cell phones and notebooks are discarded within their useful life, as perceived by consumers. While there is little research on consumer perceptions and disposal behavior of electrical and electronic waste in the literature, the results reveal the need for awareness campaigns regarding recycling and disposal, and have the potential to provide important information for policymaking and sustainable development.
The consumption and the perception of lifetime of electroelectronics due to the pandemic caused by Covid-19, between 2020 and 2023, in the state of São Paulo
Keywords: Obsolescência Programada; Resíduo de Equipamento Eletroeletrônico; Consumo de Eletroeletrônico; Obsolescência Psicológica; Scheduled Obsolescence; Waste Electronic Equipment; Consumer Electronics; Psychological Obsolescence; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA DO PRODUTO